Mass distribution of sputtered cathode material in the reflex discharge along the magnetic field mirror configuration - Kovtun, Yu.V; Skibenko, E.I.; Skibenko, A.I.; Kuprin, A.S.; Ozerov, A.N.; Syusko, E.V.; Yuferov, V.B. (Вопросы атомной науки и техники, 2016)
The paper is concerned with the distribution of cathode material sputtered under the action of the pulsed reflex discharge plasma and deposited on the anode surface (vacuum chamber) by means of a set of discrete receiving plates. Correlative relationship has been found between the weight gain increase of the receiving plates due to the deposition of cathode material (Ti) particles on them and the increasing magnetic field regions. The maximum possible sputtering yield Ycurr has been evaluated. The authors have deduced parametric dependences of the sputtering ratio on the power function exponent that determines the shape of the radial plasma-density profile, and also, on the magnetic field induction value. Досліджено розподіл розпорошеного матеріалу катодів під впливом плазми імпульсного відбивного розряду і осаджуваного на поверхні анода (вакуумної камери) за допомогою набору дискретних приймальних пластин. Встановлено кореляційний взаємозв’язок збільшення приросту маси приймальних пластин за рахунок осадження на них часток катодної речовини (Ti) і областей наростаючого магнітного поля. Проведена оцінка величини максимально можливого коефіцієнта розпорошення Υcurr. Одержані параметричні залежності коефіцієнта розпорошення від показника степеневої функції, який визначає форму радіального профілю густини плазми, і від величини індукції магнітного поля. Исследовано распределение распыленного материала катодов под воздействием плазмы импульсного отражательного разряда и осаждаемого на поверхности анода (вакуумной камеры) с помощью набора дискретных приемных пластин. Установлена корреляционная взаимосвязь увеличения прироста массы приемных пластин в результате осаждения на них частиц катодного вещества (Ti) и областей нарастающего магнитного поля. Проведена оценка величины максимально возможного коэффициента распыления Υcurr. Получены параметрические зависимости коэффициента распыления от показателя степенной функции, определяющего форму радиального профиля плотности плазмы, и от величины индукции магнитного поля.